How to Conduct a Bayesian Network Meta-Analysis - Hu, Dapeng; O'Connor, Annette M.; Wang, Chong; Sargeant, Jan M.; Winder, Charlotte B. (Frontiers in Veterinary Science, 2020)
Network meta-analysis is a general approach to integrate the results of multiple studies in which multiple treatments are compared, often in a pairwise manner. In this tutorial, we illustrate the procedures for conducting a network meta-analysis in the Bayesian framework using example data. Our goal is to describe the workflow of such an analysis and to explain how to generate informative results such as ranking plots and treatment risk posterior distribution plots. The R code used to conduct a network meta-analysis in the Bayesian setting is provided at GitHub.